Public perceptions of child protection programmes in Zimbabwe: Towards strategies to Improve the full realisation of children's rights - Ndondo, Solomon (Department of Sociology, 2024)
The study focused on the evaluation of children's rights as a vulnerable group and how they are protected in Zimbabwe. The study focused on rights to education, health, water, food, a safe environment and protection from sexual exploitation. The objectives of the study were to find out how people in Zimbabwe viewed the rights accorded to children, to establish whether the current rights of children in Zimbabwe were informing policy design and implementation, to identify actors involved in the protection of children's rights and to suggest interventions which could be put in place to ensure that children's rights are adequately protected. A mixed research design was used in this study which included qualitative data from interviews and quantitative data analysis which utilised survey data from Afrobarometer on attitudes regarding rights and vulnerability. Interviews were conducted with a purposive sample of key informants (n=25), including 14 ordinary Zimbabweans (7 in rural and 7 in urban areas), 2 officials from each of four non-governmental organisations (World Vision, Plan International, Human Rights Services Commission and Girl Child Network) and 3 politicians from the mainstream political parties (ZANU PF, Citizens Coalition for Change and Movement for Democratic Change). Data was analysed through descriptive statistics and themes. The findings of the study highlighted that most participants know children's rights and how they should be protected. International conventions define some rights but may not fully represent African interests. Zimbabweans have a positive view of children's rights but have reservations about their protection. Certain policies for children's rights are not fully functional due to cultural, political, and economic reasons. The Welfare Council policy helps children, but assistance varies based on location, favouring urban areas. Existing policies in Zimbabwe may not be effectively implemented, leaving some children vulnerable. It is recommended that there is a need for the government of Zimbabwe to redefine the rights of children and ensure that they reflect the norms and values of local culture. This will make it easy to interpret and design relevant policies. Other stakeholders' resistance to the definition of these rights accorded by international conventions made it challenging to successfully protect rights. It is recommended that the government of Zimbabwe should carry out public hearings when formulating various policies regarding protecting children's rights. This is based on the fact that some of the respondents showed limited knowledge regarding the current policies meant to protect children. Further recommendation is made on the need for the government to seek financial help from non-governmental organizations to ensure full policy implementation. This follows the finding that policies meant to safeguard children's rights are currently present but lack full implementation due to financial challenges. Distribution of financial and infrastructural resources should spread to rural areas to ensure enhanced protection of children's rights in rural areas. Ultimately, there is a need to ensure that government implements policies equally and reduce the vulnerability of children.